John Wilson’s Interview of John Parris, June 5th, 1975, HL_MSS17-03_19_46 - Norwood, Jo (2025)
This edition is created from the audio file containing a conversation between John Wilson and John Parris. Within the audio recording John Wilson relays to John Parris information on the death of Oscar “Ott” Lloyd Blair. Wilson asks Parris about a story he did on Blair, but Parris says he never did such a story. The two of them go back and forth for a minute about this, and Wilson mentions seeing the story in a newspaper. Wilson goes on to ask Parris to help him set a foundation and scholarship at Lees-McRae College in honor of Blair.